VISUAL CV PROGRAMS ON ARAB SATELLITE CHANNELS, RAWAFED (TRIBUTARIES) PROGRAM IN AL ARABIYA CHANNEL AS A MODEL-ANALYTICAL STUDY - Suhad Adnan Challoop (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
Resulted from the interaction between technology communication modern and mass media visual art curriculum vitae are new from the programs of television called by experts Media: Biography of self - visual. The art curriculum vitae visual one arts television news that attracted the interests contained in the information and pictures of documentary the videos turned the biography of the elite intelligentsia of intellectuals and famous art and culture and knowledge to the material of television accompanied by dialogues shed lights on the most prominent stations His biography self. Deals with this research subject curriculum vitae visual from aspects of theoretical and applied in satellite channels Arabic. It has chosen the researcher program streams, which broadcast channel Arab satellite model applied to study them. The research adopted the descriptive and analytical approach and the method of content analysis after selecting a sample from the episodes of that program. The research came out with a set of results and recommendations.